Conditionally lethal and recessive UGA-suppressor mutations in the prfB gene encoding peptide chain release factor 2 of Escherichia coli. - Kawakami, K (1988)
Strains carrying mutations in the prfB gene encoding peptide chain release factor 2 of Escherichia coli were isolated. prfB1, prfB2, and prfB3 were selected as suppressor mutations of a lacZ (UGA) mutation at 37 degrees C, one of which, prfB2, is temperature sensitive in growth. A prfB286 strain was selected as a conditionally lethal mutant which grows at 32 but not at 43 degrees C and was shown to have UGA-suppressor activity. All the mutations are recessive UGA-suppressors. These data indicate that release factor 2 is essential to E. coli growth and that all mutants isolated here trigger suppression of the UGA codon.